1991
DOI: 10.1016/1010-7940(91)90226-a
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolism in patients with pericardial valves in the absence of chronic anticoagulation: 12 years' experience

Abstract: Between January 1977 and January 1989, 465 pericardial bioprostheses were implanted in 424 patients. The mean age of patients was 59.1 years (range 16-81 y.) At the time of surgery, 68% of the patients suffered from chronic atrial fibrillation. Mitral valve replacement was performed in 167 patients, aortic valve replacement in 216, multiple replacement in 40 (36 mitral and aortic, 3 mitral and tricuspid, and 1 mitral, aortic and tricuspid), and 1 pulmonary valve replacement. The different types of pericardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Noteworthy, the oversulfation level found here is comparable to that of DS from marine ascidians (50–70%) also studied for its thrombin inhibitory activity [37]. All that could be the rationale behind the still unexplained low thrombogenicity potential of pericardial valve xenografts making the chronic anticoagulation treatment unnecessary in such patients [38]. Moreover, this finding is in good agreement with published data which described the presence of a low-molecular-weight dermatan sulfate proteoglycan in bovine pericardial tissue [39].…”
Section: Discussionmentioning
confidence: 68%
“…Noteworthy, the oversulfation level found here is comparable to that of DS from marine ascidians (50–70%) also studied for its thrombin inhibitory activity [37]. All that could be the rationale behind the still unexplained low thrombogenicity potential of pericardial valve xenografts making the chronic anticoagulation treatment unnecessary in such patients [38]. Moreover, this finding is in good agreement with published data which described the presence of a low-molecular-weight dermatan sulfate proteoglycan in bovine pericardial tissue [39].…”
Section: Discussionmentioning
confidence: 68%
“…The results of the present and other studies (4,5,16,26) suggest that for 19 mm pericardial bioprostheses in aortic position, mounting of the pericardium outside the support frame is haemodynamically somewhat more satisfactory than the inside mounting used in the Carpentier-Edwards valve (although we know of no study with rigorous approach to this question in a large patient sample, and the precise clinical implications of the difference are unclear).…”
Section: Discussionmentioning
confidence: 47%
“…Edmunds et al 43 showed that there was a need for anticoagulation in 40 to 60% of the patients with biological prosthesis in mitral position; the incidence of thromoembolic episodes is greater in the first three months of bioprosthesis implant, the atrial fibrillation increases the risk of thromboembolic complications, the role of the presence of atrial thrombi, the size of left atrium and the history of previous embolic events is not clear yet in the increase of incidence of thromboembolic events. The atrial fibrillation is the main factor identified in the literature as responsible for the increase of risk of systemic thromboembolism in patients with mitral valvopathy [44][45][46][47] . Reports in the literature show a lower incidence of thromboembolic events in patients with bovine pericardium or dura mater bioprostheses in comparison with porcine biosprostheses [48][49][50] .…”
Section: Discussionmentioning
confidence: 99%